CompTIA Linux+ (Exam LX0-102) - Rogers, Bobby; Safari eBooks ([S.l.] : Virtual Training Company, 2013)
"Veteran VTC instructor Bobby Rogers guides the student through an in-depth review of the Linux+ LX0-102 exam from a very practical, hands-on point of view. This course provides step-by-step demonstrations of the different commands, utilities, and configuration options a candidate really needs to know before taking the exam. The course covers all domains and objectives required for the exam, including scripting, networking, system administration, managing user accounts, and security. To begin learning today, simply click on the movie links."--Resource description page.
Title from resource description page (viewed Mar. 28, 2014).
Presenter, Bobby Rogers.
Keywords: Linux; Electronic data processing personnel -- Certification; Operating systems (Computers) -- Examinations; Electronic books